Colon capsule endoscopy in colorectal cancer screening: a randomised controlled trial. Issue 1 (29th June 2020) - Kaalby, Lasse; Deding, Ulrik; Kobaek-Larsen, Morten; Havshoi, Anne-Line Volden; Zimmermann-Nielsen, Erik; Thygesen, Marianne Kirstine; Kroijer, Rasmus; Bjørsum-Meyer, Thomas; Baatrup, Gunnar
Abstract : Introduction: The use of capsule endoscopy has become an approved method in small bowel diagnostics, but the same level of integration is not seen in large bowel diagnostics. We will use colon capsule endoscopy (CCE) as a filter test in colorectal cancer (CRC) screening between the faecal immunochemical test (FIT) and colonoscopy. We aim to investigate the clinical performance, population acceptability, and economic implications of the procedure in a large-scale clinical trial. Methods and analysis: We will randomly allocate 124 214 Danish citizens eligible for participation in the national CRC screening programme within the Region of Southern Denmark to either an intervention group or a control group. Prior to submitting a FIT, citizens randomised to the intervention group will be informed about their opportunity to undergo CCE, instead of colonoscopy, if the FIT is positive. Suspected cancers; >3 adenomas <10 mm in size, 1 adenoma >10 mm in size or >4 adenomas regardless of size, detected during CCE will generate an invitation to colonoscopy as per regular screening guidelines, whereas citizens with suspected low risk polyps will re-enter the biennial screening programme. Citizens with no CCE findings will be excluded from screening for 8 years. In the control group, citizens will follow standard screening procedures. Ethics and dissemination: All participants must consent prior to capsule ingestion. All collected data will be handled and stored in accordance with current data protection legislation. Approvals from the regional ethics committee (ref. S-20190100) and the Danish data protection agency have been obtained (ref. 19/29858). Trial registration details: The study has been registered with ClinicalTrials.gov under: NCT04049357 .